PENGARUH KECERDASAN EMOSIONAL MELALUI KUALITAS PELAYANAN TERHADAP KINERJA PERAWAT DI RSUD HAJI MAKASSAR - Alfian Alfian; Masriadi Masriadi; Ikhram Hardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study focuses on a comprehensive exploration of the impact of emotional intelligence on nurses’ performance, with service quality functioning as a mediating variable at the Regional General Hospital (RSUD) Haji. The background of this research is grounded in the critical role of nurses as the frontline providers in medical services, where emotional elements and interpersonal relationships significantly influence both the quality of care and work effectiveness. Emotional intelligence in this study is examined through five core dimensions: self-awareness, self-regulation, motivation, empathy, and social skills. A quantitative approach was employed using a cross-sectional design. Data were collected through the distribution of closed-ended questionnaires using a Likert scale to 143 nurses working at RSUD Haji. The research instruments underwent validation and reliability testing prior to deployment. Data analysis was conducted using path analysis to explore both direct and indirect relationships among variables, and to understand the mediating role of service quality in the relationship between emotional intelligence and nurses’ performance. The findings reveal that the dimensions of self-regulation and social skills have a significant impact on service quality. Furthermore, social skills also exert a direct influence on nurses’ performance. Service quality clearly serves as a significant mediator in the relationship between emotional intelligence and performance, particularly in the dimensions of self-regulation and social skills. These results suggest that enhancing emotional intelligence—especially in terms of self-control and social interaction—can contribute to improved service delivery by nurses, thereby positively affecting their overall performance. This study offers both theoretical and practical contributions to the development of human resources in the healthcare sector and serves as a reference for hospital management in designing training programs and interventions focused on strengthening the emotional intelligence of healthcare professionals. Keywords: emotional intelligence, service quality and nurse performance